Matching-adjusted indirect comparison of tislelizumab plus lenvatinib versus sintilimab plus bevacizumab biosimilar as first-line treatment for unresectable hepatocellular carcinoma - Wang, Kunyuan; Liu, Chang; Song, Xiaoling; Zhao, Na; Zheng, Xin (Frontiers in Immunology, 2025)
BackgroundProgrammed cell death-1/programmed cell death-ligand 1 (PD-[L]1) inhibitors plus bevacizumab (or biosimilars) or tyrosine kinase inhibitors (TKIs) have been widely used for the first-line treatment of patients with unresectable hepatocellular carcinoma (uHCC). However, no head-to-head trials have compared the efficacy outcomes between these two combination regimens. Therefore, an unanchored matching-adjusted indirect comparison (MAIC) was conducted to evaluate the comparative efficacy of tislelizumab plus lenvatinib versus sintilimab plus bevacizumab biosimilar.MethodsIndividual patients from the BGB-A317-211 study (NCT 04401800) for tislelizumab plus lenvatinib were adjusted to match the population from the ORIENT-32 (NCT 03794440) for sintilimab plus bevacizumab biosimilar through an unanchored MAIC. Odds Ratios (ORs) of objective response rates (ORR) and disease control rates (DCR), and hazard ratios (HRs) of progression-free survival (PFS) and overall survival (OS) were evaluated to quantify the relative treatment effect between the two treatment regimens after population matching. Sensitivity analyses were performed by sequentially removing one variable in the matching and adjusting the population through simulated treatment comparison (STC).ResultsAfter matching, baseline characteristics were balanced between the tislelizumab plus lenvatinib group (effective sample size [ESS] = 49, ESS/N = 79.03%) and sintilimab plus bevacizumab biosimilar group (N = 380). MAIC analysis indicated that tislelizumab plus lenvatinib group showed significantly higher ORR per RECIST v1.1 (OR = 2.56, 95% CI 1.40-4.63; p = 0.0027), higher DCR (OR = 3.81, 95% CI 1.62-11.20; p = 0.0013), longer PFS (HR = 0.56, 95% CI 0.37-0.84, p = 0.0054), and improved OS (HR = 0.43, 95% CI 0.25-0.74, p = 0.0023), compared to sintilimab plus bevacizumab biosimilar group. Sensitivity analysis by two different methods supported the findings from the primary MAIC analysis.ConclusionsThis MAIC analysis demonstrated that tislelizumab plus lenvatinib achieved superior efficacy, with higher ORR and longer PFS and OS compared to sintilimab plus bevacizumab biosimilar in untreated Chinese patients with uHCC.